Racial-ethnic relations and the question of disability in Brazilian children's literature: an experiment in training of teachers - Edna Martins; Erica Aparecida Garrutti de Lourenço (Universidade Federal de Santa Maria, 2013)
Considering the paradigm of the inclusive education, the regular school should organize itself to welcome and offer objective conditions of learning for all students. With an emphasis on how diversity is represented for children through children's literature, this report presents the experience with the subject "Pedagogical Programmed Practices: Diversity and Literature - representations of blackness and disability for children" in the formation of first year academic students of Pedagogical Course of São Paulo Federal University, Guarulhos Campus. This study focused on the discipline of theoretical frameworks that deal with the diversity and, more specifically, ethnic-racial and disability in children's literature. The experience points to the importance of initiatives aimed at developing activities focused on understanding the diversity in the formation of critical thinking in training of teachers.